PERKEMBANGAN MODUS OPERANDI KEJAHATAN SKIMMING DALAM PEMBOBOLAN MESIN ATM BANK SEBAGAI BENTUK KEJAHATAN DUNIA MAYA (CYBERCRIME) - Dian Alan Setiawan (Faculty of Law - Tarumanagara University, 2019)
The development of technology and the internet does not always produce positive things. Negative things that are side effects include the crime of skimming (theft of customer data) which is one type of crime in cyberspace. Lately Indonesia is enlivened with breaking ATM news that occurred in various regions in Indonesia. The customers suddenly lose their account balance due to being burglarized by irresponsible people. ATM piercing technique is known as ATM Skimmer Scan technique. ATM machine piercing (Automated Teller Machine) using Skimmer, which is a customer data thieves. The modus operandi of bank breakers is installing skimmer in ATM mouth. After the customer data obtained, the perpetrator just insert into the ATM card. burglars will freely drain the customer's money. Problems that arise is the development of modus operandi crime skimming in the case of bank burglary bank as a form of cybercrime (cybercrime) And Efforts / Legal Steps in Tackling Crime Use of Information Systems and Electronic Transactions. This research is legal research using conceptual approach and statue approach which will review Law Number 11 Year 2008 regarding Information and Electronic Transaction. Based on the method used, it is known that the modus operandi of criminal skimming in ATM bankruptcy as a form of cyber crime and the application of article in Law Number 11 Year 2008 regarding Information and Electronic Transaction as an effort / step in tackling the crime of Information System Use and Electronic Transactions.